Interval Debulking Surgery in Ovarian Cancer - Singh, Meeta; Jha, Rajshree; Dhakal, Samjhana (Nepal Journal of Obstetrics and Gynaecology, 2011)
Primary debulking surgery’s (PDS) role in ovarian cancer there is no dispute, as the currently accepted management of treatment of advanced stage ovarian cancer is PDS in order to achieve an optimal cytoreduction as the amount of residual tumour is one of the most important prognostic factors for survival of women with epithelial ovarian cancer. Several authors have reported PDS is associated with high mortality and morbidity rates, when an optimal surgical procedure, defined as a removal of tumours to < 1to 2 cm in size, required for advanced stage disease (III to IV). So interval debulking sugery (IDS) should be performed in unresectable cases or in the advanced ovarian cancers. However the role of IDS is still not well defined, at present where PDS is feasible and permits a minimal residual tumour to achieve an optimal cytoreduction with an acceptable morbidity, it should be performed in patients with stage II up to IIIC disease with minor carcinomatosis. IDS should be performed in the case of patients with massive unresectable cases. The preliminary results so far reported should be confirmed by a randomized study or level1evidence being conducted by the EORTC (European Organisation for Research and Treatment of Cancer) group to reinforce the randomized study of Maria et al before recommending IDS in cancer of ovary Keywords: IDS, PDS, unrespectable ovarian cancer DOI: http://dx.doi.org/10.3126/njog.v6i1.5244 NJOG 2011; 6(1): 3-6